PERISTIWA 1 OKTOBER 1965 SEBAGAI PUNCAK PERGOLAKAN POLITIK DI TAHUN 1950-AN - Agung, Dewa Agung Gede (Jurnal Sejarah dan Budaya, 2010)
Abstract: Main assumption that PKI ( IndonesianCommunis Party ) as single factor behind the October 1st, 1965 tragedy becoming formal law decision nowadays in Indonesia. Tracing this tragedy need an understanding into politics structure applied from year 1950 until 1965 in Indonesia. Learning history are based on continuity and chronological so it has applied on this tragedy. This tragedy popular with G30S/PKI and relevant with historical event such as Liberal Democracy Periods (1950 â 1957) and Guided Democracy Periods (1957 â 1965). G30S/PKI are accumulate tragedy caused by political interest on that period